The system architecture of E-braille by using the microcontroller and external controller unit - Burhan, Muhammad Mansor; Toha, Siti Fauziah (Asian Research Publishing Network (ARPN), 2016)
Blind people always have difficulties to access some information. So the braille language symbols are used to overcome this problem. With this modern technology, the refreshable braille cell was created. This cell is using piezoelectric concept. This refreshable braille cell can refresh the character. The pin for each braille cell is controlled by using piezoelectric bimorph. This will make the pin to rise and down. In this paper, the refreshable braille cell is controlled by the Arduino microcontroller and gets command from the Braille Key Module. The software use for this program is Arduino which use C+ language. The system is tested and successful.